[Retracted] Chronic Recurrent Multifocal Osteomyelitis with Concomitant Features of Juvenile Idiopathic Arthritis - Tsitsami, Elena; Dermentzoglou, Vasiliki; Moschovi, Mary; Chrousos, George P. (Case Reports in Rheumatology, 2011)
We report a case of a 13-year-old girl with chronic recurrent multifocal osteomyelitis (CRMO) who developed severe arthritis in four different joints within the first year from the onset of the disease. Her multiple vertebrae lesions showed significant amelioration after a 2-month treatment with prednisolone. In parallel, the initial severe symmetrical arthritis of both knees showing overt synovitis and joint effusion, in the absence of lesions in the metaphyses of the femur or the tibia, responded remarkably well in intra-articular triamcinolone hexacetonide injections. However, upon discontinuation of prednisolone, the patient developed severe arthritis of her right ankle and the proximal interphalangeal joint of her right middle finger. Thus, prednisolone was reinitiated combined with methotrexate, and the patient went into remission, which persists one year after prednisolone tapering. The appearance of arthritis in both knees in the absence of bone lesions and the emergence of severe arthritis of the ankle after remission of spinal bone lesions suggest that CRMO and juvenile idiopathic arthritis may coexist and be causally related.